Sexual desire, sexual satisfaction and personality traits s predictors to cyber sexting among emerging adults in Malaysia - Lee, Xin Kei (2020)
The enormous advancement of the Internet which was risky to prompt the growth of cybersexting behaviour. The current research was correlational, descriptive study that aimed to examine the predicting effects of sexual desire, sexual satisfaction and personality traits (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) on cybersexting behaviour among emerging adults in Malaysia. A total of 332 participants were recruited in this research by using non-probability sampling method specifically, purposive sampling by distributing the survey via social media and through paper and pencil method. The recruited participants were Malaysians emerging adults aged from 18 to 25 years old (M = 21.60 years). There were slightly more female (N = 184, 55.4%) than male respondents in the current study (N = 148, 44.6%). Overall, there were 31 Malays (9.3%), 270 Chinese (81.3 %), 30 Indians (9.0%) and one respondent from others ethnicities (0.3%). The findings revealed that sexual desire and agreeableness were significant predictors towards cybersexting behaviour among Malaysian emerging adults, while personal sexual satisfaction, openness to experience, extraversion, conscientiousness and neuroticism were not significant predictors of cybersexting behaviour. Present study contributed the novel findings to help increase the knowledge regarding this topic. The information gathered from this research will be useful for relevant authorities to implement effective policies and interventions in order to protect emerging adults from sexual predators and increase awareness on the prevalence and risks of cybersexting behaviour.